Methodological and practical analysis of the prerequisites and starting conditions for the business transformation process - Valinkevych , N.; Molodko, O.; Boshtan , A.; Shtyl , A.; Verchenko , V. (Ways to Improve Construction Efficiency, 2024)
The article is devoted to the methodological and practical analysis of the prerequisites and starting conditions for the business transformation process. In today's conditions of globalization and rapid changes in the market, businesses are forced to constantly adapt their strategies and operational processes in order to remain competitive. Business transformation, as a process of significant changes, requires a clear understanding of the prerequisites that determine the success of such changes. This includes not only the analysis of external factors, such as changes in the economic environment, new technologies and regulations, but also internal aspects of the business: the structure of the organization, corporate culture, management practices and financial stability. The article analyzes the key stages necessary for successful business transformation and offers practical recommendations for companies that want to carry out this transformation effectively and with minimal losses. The importance of building adaptive strategies, flexible management models and active implementation of innovations to ensure successful transformation is emphasized. The use of various change management methods is also considered, in particular, the use of strategic management principles, monitoring and evaluation of the results of transformation initiatives. The article concludes with the conclusions that successful transformation requires a comprehensive approach that includes management of all levels of the business and the ability to adapt to a rapidly changing environment. Since transformation requires resources and time, the article emphasizes the importance of change planning and risk management to achieve sustainable development and increase the efficiency of the company. Additionally, for successful transformation, it is important to invest in improving the skills of employees, adapt to new technologies and continuously improve internal processes. Special attention is also paid to maintaining open communications between all levels of the organization to ensure the integration of changes and minimize resistance to change. The implementation of these approaches can help companies not only remain competitive, but also occupy leading positions in the market.